2016
DOI: 10.1530/rep-16-0236
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of pregnancy-specific glycoproteins in human and horse

Abstract: Pregnancy-specific glycoproteins (PSGs) are members of the carcinoembryonic antigen cell adhesion molecule (CEACAM) family that are secreted by trophoblast cells. PSGs may modulate immune, angiogenic and platelet responses during pregnancy. Until now, PSGs are only found in species that have a highly invasive (hemochorial) placentation including humans, mice and rats. Surprisingly, analyzing the CEACAM gene family of the horse, which has a non-invasive epitheliochorial placenta, with the exception of the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 45 publications
(46 reference statements)
1
36
1
Order By: Relevance
“…In contrast to the equine CEA gene family where we could not identify two of the conserved CEACAMs e.g. CEACAM18 and CEACAM20 11,19 , in cattle all conserved CEACAMs i.e. CEACAM1, CEACAM16, CEACAM18, CEACAM19 and CEACAM20 could be identified in the NCBI genome database.…”
Section: Discussioncontrasting
confidence: 91%
“…In contrast to the equine CEA gene family where we could not identify two of the conserved CEACAMs e.g. CEACAM18 and CEACAM20 11,19 , in cattle all conserved CEACAMs i.e. CEACAM1, CEACAM16, CEACAM18, CEACAM19 and CEACAM20 could be identified in the NCBI genome database.…”
Section: Discussioncontrasting
confidence: 91%
“…Indeed this is the case for bat PSGs. Remarkably, the structure of bat PSGs is very similar to the PSGs recently found in the horse [ 21 ] suggesting that both have a common ancestor. Indeed the phylogenetic relationship of bats within Laurasiatheria is still a matter of debate, however several lines of evidence point to a close relationship of bats and horses [ 23 ].…”
Section: Discussionsupporting
confidence: 64%
“…However, a few exceptions of this rule exist [ 11 ]. Recently, we have identified an expanded CEA gene family in the horse the expansion of which is due to the amplification of genes coding for secreted PSG-like CEACAMs [ 21 ]. In addition, there are reports indicating that the CEA gene family has been expanded in certain microbats [ 22 ], namely in Myotis lucifugus [ 11 ] and in Myotis davidii [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the horse genome, CEACAM1 and seven CEACAM1 paralogs exist, which contain exons coding for transmembrane domains [ 15 ]. Phylogenetic analyses using nucleotide sequences of equine CEACAM transmembrane (TM) domain exons and of human CEACAM1 and CEACAM3 , respectively, resulted in trees that comprise two deep clades, one containing human CEACAM1 TM sequence and 6 closely related equine TM sequences and the other containing human CEACAM3 TM sequence and a single equine TM sequence of CEACAM41 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, efficient mechanisms must exist for the diversification of signaling capacities, if a duplication of inhibitory receptors is envisaged. We have recently reported that convergent evolution within the CEA gene families of humans and the horse had led to a similar expansion of secreted pregnancy-specific glycoproteins (PSG), which are a subgroup of CEACAM1 paralogous genes [ 15 17 ]. Obviously, secreted CEACAMs, which do not contain a transmembrane and cytoplasmic domain do not transmit signals into the cell and therefore are functionally different from the ancestral inhibitory receptor CEACAM1.…”
Section: Introductionmentioning
confidence: 99%